2007
DOI: 10.1016/j.curtheres.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Helicobacter pylori in symptomatic patients and detection of clarithromycin resistance using melting curve analysis

Abstract: The prevalence of H pylori infection was 53.3% for the symptomatic patients in this study, and 47.5% of the isolates showed clarithromycin resistance using melting curve analysis. The PCR-based system used in this study was accurate for the detection of H pylori infection as well as clarithromycin susceptibility testing directly in biopsy specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The sensitivity of culture method to detect H. pylori, in adult population, ranges from 62.7% to 96.3% in the studies performed [8,10,12].…”
Section: 68%mentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of culture method to detect H. pylori, in adult population, ranges from 62.7% to 96.3% in the studies performed [8,10,12].…”
Section: 68%mentioning
confidence: 99%
“…Our results are less significant if compared to other published data in which higher percentages of positive cultures were obtained, except one. Kaya et al reported the sensitivity for H. pylori culture as 22.5%, and the specificity as 97.1%[10].…”
mentioning
confidence: 99%
“…There were no other data to compare the results [31]. There were no other data to compare the results [31].…”
Section: Prevalence Of Primary Clarithromycin Resistancementioning
confidence: 99%
“…For the north region of Turkey, there was only one study, and the primary clarithromycin resistance rate was reported as 30%. There were no other data to compare the results [31]. The highest primary clarithromycin resistance rates were obtained from the central (50%; 2007) [25] and west regions (48.2%; 2003-2004) [15].…”
Section: Prevalence Of Primary Clarithromycin Resistancementioning
confidence: 99%
“…In fact, we elected to include this step in the study for safety reasons to detect any serious underlying condition that can be missed in some cases (30), as well as to further validate the usefulness and accuracy of the alarm features mentioned in the guidelines. (iii) In Turkey, clarithromycin resistance has a prevalence of around 24-48% (31)(32)(33). The use of a triple treatment that included clarithromycin for the eradication of H. pylori may have resulted in both a lower eradication rate and a lower proportion of patients who achieved sufficient overall symptom relief.…”
Section: Limitations Of This Trialmentioning
confidence: 99%